PENGARUH MOTIVASI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT ASTRA OTOPART (MOTOQUICK) TANGERANG SELATAN - Vika Andriani; Haidilia Maharani (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of motivation and the physical work environment on employee performance at PT. Astra Otopart (Motoquick) South Tangerang. partially or simultaneously. The method used is quantitative. The sampling technique used saturation and the sample obtained in this study was 60 employees. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, coefficients, coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research show that motivation (X1) has a significant effect on employee performance (Y) with the regression equation Y = 9.512 + 1.185 X1 + 0.352 In X2, the value obtained is t count > t table, namely (3.449 > 1.669), thus the variables X1 and Which means that motivation variables and the physical work environment simultaneously influence employee performance. also obtained through simultaneous hypothesis testing f table > f count, namely (64.314 > 2.75). Which means that motivation variables and the physical work environment simultaneously influence employee performance. Analysis of the coefficient of determination shows that 66.8% of the influence of fulfillment and motivation variables has on employee performance, while 33.2% depends on other factors not included in this research.